Implementasi Projek Penguatan Profil Pelajar Pancasila Untuk Memperkuat Cinta Budaya Dan Daerah Melalui Kegiatan Sapoe Nyunda - Intan Oktaviani Agustina (Education : Jurnal Sosial Humaniora dan Pendidikan, 2023)
This research is about the Implementation of the Project to Strengthen Pancasila Student Profiles to Strengthen Love for Culture and the Region through Sapoe Nyunda Activities. This independent curriculum is different from the previous curriculum, namely there is a Project to Strengthen Pancasila Student Profiles. This project is to improve student character as a Pancasila profile through projects in the surrounding environment. Implementation of the Project to Strengthen Pancasila Student Profiles at Al-Ma'soem Elementary School through the sapoe nyunda activity, namely rampak sekar to strengthen a sense of love for culture and the region. Data collection techniques used are in the form of interviews and documentation. The results of the study showed that teachers and students were very enthusiastic about sapoe nyunda activities. Implementation of the Pancasila Student Profile Strengthening Project is practiced directly so that learning will be more meaningful and memorable for students.